Use of Appendix as Neoureter- A Ray of Hope - Parveen Kumar; Yogesh Kumar Sarin (EL-Med-Pub, 2017)
A case of antenatally diagnosed hydronephrosis (later known to be PUJO complicated with urinoma and associated with hypoplasia of entire ureter) was treated using vermiform appendix as replacement.